2003
DOI: 10.1002/ddr.10190
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotection with pre‐ and postischemic adenosine and A3 receptor activation: Differing mechanisms and effects on necrosis versus stunning

Abstract: The importance of pre-versus postischemic treatment in adenosine-mediated cardioprotection is unclear. We characterized effects of pre-and postischemic adenosine or A 3 adenosine receptor (A 3 AR) agonism in Langendorff perfused mouse hearts subjected to 20 min global ischemia and 45 min reperfusion. In untreated hearts, diastolic pressure remained elevated at 2172 mmHg, ventricular pressure development recovered to 7573 mmHg (50% of pre-ischemia), and 2473 IU/ lactate dehydrogenase (LDH) was lost. Adenosine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Inhibitory effects of 5-HD may reflect antagonism of these actions and/or activation to 5-HD-CoA with modulation of fatty acid oxidation and mitochondrial metabolism (97). Given the common effects of adenosine and diazoxide (77,207,210,228) and inhibition of adenosinergic protection by 5-HD (113,118,207,210,228), it is possible acute adenosinergic protection involves the above-mentioned inhibitory actions on ROS generation, mitochondrial metabolism, and nucleotide-dependent enzymatic activity as opposed to mitoK ATP activation. In this respect, a number of investigations verify that adenosine receptor activation modifies mitochondrial energy metabolism (2, 43, 79, 112) and inhibits ROS generation (210) in ischemic-reperfused myocardium.…”
Section: Molecular Basis Of Receptor-mediated Cardioprotectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inhibitory effects of 5-HD may reflect antagonism of these actions and/or activation to 5-HD-CoA with modulation of fatty acid oxidation and mitochondrial metabolism (97). Given the common effects of adenosine and diazoxide (77,207,210,228) and inhibition of adenosinergic protection by 5-HD (113,118,207,210,228), it is possible acute adenosinergic protection involves the above-mentioned inhibitory actions on ROS generation, mitochondrial metabolism, and nucleotide-dependent enzymatic activity as opposed to mitoK ATP activation. In this respect, a number of investigations verify that adenosine receptor activation modifies mitochondrial energy metabolism (2, 43, 79, 112) and inhibits ROS generation (210) in ischemic-reperfused myocardium.…”
Section: Molecular Basis Of Receptor-mediated Cardioprotectionmentioning
confidence: 99%
“…Nonetheless, postischemic contractility is enhanced by exogenous and endogenous adenosinergic stimuli under conditions of limited or no detectable cell death (149,161,165,200,201,210,215,234,235,246,258,318). In addition, recent work has identified differential effects of adenosine (77,228) and adenosinergic preconditioning (226) on oncosis versus contractile function, supporting amelioration of both injuries via different pathways.…”
Section: Protection Against Reversible Versus Irreversible Injuries Mmentioning
confidence: 99%
See 1 more Smart Citation
“…12) However, there was no detectable protective effects of A 2B adenosine receptor on coronary dysfunction. 34) Flood et al 32) found substantial protection against coronary dysfunction via A 1 adenosine receptor activation by endogenous adenosine. Exogenous A 3 adenosine receptor activation further limits dysfunction and improves post-ischemic vasoregulation.…”
Section: Discussionmentioning
confidence: 99%
“…30,31) A 2 adenosine receptor activation was found to protect against postischemic vascular endothelial injury. 10,32,33) Protection via A 2A adenosine receptor sub-type likely involved modulation of blood-cell dependent processes. 12) However, there was no detectable protective effects of A 2B adenosine receptor on coronary dysfunction.…”
Section: Discussionmentioning
confidence: 99%